Ética na gestão de pessoas - Lopes, Jerisnaldo Matos (2010)
In this paper we intend to analyze the management of people in business in the area of corporate social responsibility and its consequent relationship to contemporary ethics. We made a brief elaboration of the conceptual and historical aspects involving the dilemmas and the needs of administrative staff, considering ethical issues from the various elements that comprise a particular business atmosphere. Part of the healthy life of an enterprise is linked to intelligence concerning the administrative aspects of social responsibility, that is, their ability to meet the needs of many elements that make up their organizational system and its local system, where it based its action. This includes links with the immediate context and the wider context, consumers themselves of their products. A good relationship with this system allows companies to excel on the issues, often, arising from own performance and place of business, e.g., the environment, labor issues or certain foreign investments to their own nature. Evaluate this set of situations and their ethical implications is the purpose of this study.